Peta Jalan Implementasi Target 4.7 SDGs di Kalimantan Timur: Kolaborasi Lintas-Sektor untuk Pendidikan Inklusif Berkelanjutan - Lukman Hakim; Priguna Adhitama; Riko Dwi Suharto Putro; Enos Paselle; Cathas Teguh Prakoso (Inovasi, 2026)
Target 4.7 of the Sustainable Development Goals (SDGs) emphasizes the importance of education for sustainable development, global citizenship, human rights, and cultural diversity in the education system. This study aims to develop a roadmap for the implementation of Target 4.7 in East Kalimantan, emphasizing cross-sector collaboration as a strategic approach. The method used is exploratory qualitative through in-depth interviews and policy analysis of stakeholders in the education, environment, and social sectors. The study results show that East Kalimantan has great potential to integrate sustainability values into the local curriculum, supported by regional development planning documents and strong policy commitments. However, the implementation process still faces significant challenges such as institutional fragmentation, the lack of operational indicators for Target 4.7, and limited inter-sectoral coordination capacity. Recommendations from this study include the establishment of a multi-level partnership model involving local governments, academics, NGOs, and the private sector, as well as strengthening monitoring and evaluation mechanisms based on local indicators. The roadmap is expected to serve as a strategic reference for improving the effectiveness of sustainable education integration in regional policies, in line with East Kalimantan's vision of becoming an advanced and sustainable economic superhub. Through a transformative and inclusive approach, cross-sectoral collaboration is considered crucial to ensuring the systemic, measurable, and sustainable implementation of Target 4.7.